The Influence of Demographic and Migration Processes in Modern Russia on the Intellectual Security of the Nation - V. E. Chistiakova (Ekonomika Nauki)
Socio-economic growth relies heavily on the development of intellectual capital, which drives innovative transformations in society. However, modern social realities pose significant risks, including the decline of intellectual capital and the rise of humanitarian and psychological threats. In Russia, addressing negative demographic and migration trends has become a critical challenge. These trends include declining birth rates, rising mortality, an aging population, ongoing natural population decline, uneven population distribution across the country, and significant disparities in living conditions between regions. This study highlights the urgent need to address these issues, as Russia is losing highly qualified specialists due to its current demographic situation and uncontrolled labour migration. These specialists play a crucial role in building a high-quality human potential structure. The article aims to demonstrate the necessity of activating policies for demographic growth and regulating migration processes to strengthen the state’s economic power. The study identifies unfavourable demographic and migration trends in Russia, which are causing destructive processes in the development of intellectual resources and threatening the nation’s technological sovereignty.